Detection of enterotoxin-coding genes of Staphylococcus aureus isolated from hospitalized patients using a multiplex-PCR method - Vahid Ghanbarinejad; Aboozar Kazemi; Mina Zareei; Reza Heidari; Hossein Hassanian-Moghaddam (Shiraz University of Medical Sciences, 2019)
Staphylococcus aureus (S. aureus) is a pathogen in community-acquired or hospital infections. Hence, the identification of this pathogen in clinical samples is a health concern and demands continued surveillance and close monitoring. In the current study, S. aureus strains were isolated from various clinical specimens in the Shariati Hospital, Tehran, Iran. Samples were studied to discover S. aureus enterotoxin-coding genes A (sea), B (seb), C (sec), and D (sed). It was found that 21% enterotoxigenic S. aureus harbored sea gene, 39% were carried seb gene, 37% were positive for sec-gene, and 3% were carried sed gene. None of all S. aureus strains harbored more than one of the enterotoxigenic genes. Based on the data obtained from the current study, it could be suggested that seb and sec genes are good candidates for the identification of S. aureus in clinical specimens. Further investigations are required to discover the association between these genes and the pathogenicity of this bacteria, and finally using these data in clinical settings.